Citizens' E-Participation at Local Municipal Government in South Africa - Okeke-Uzodike, Obianuju E.; Dlamini, B. (Journal of Reviews on Global Economics, 2019)
The emergence of the digital revolution has obligated governments all over the world to be more accessible, effective and accountable in the provision of public services. The South Africa government has implemented various Information and Communications Technology (ICT) enabled platforms in engaging citizens in decision-making, a resultant effect of high world E-government Development Index (EGDI) rating for the country. Irrespective of the rating, the citizens have resorted to public violence as a means of communicating about unsatisfactory service delivery issues. The South African government has continued to witness numerous service delivery protests, resulting in destruction of public property, injury and death of innocent citizens. This article therefore evaluates the application of e-participation in government decision-making, using a three-dimensional framework of e-enabling, e-engaging and e-empowering. The findings show that structural challenges exist that limit the achievement of the good intentions of e-participation. The article relies heavily on existing data and focuses at local municipal level, which is considered the closest point of contact between government and citizens.